The Practicality of Geometry Learning Media based on Augmented Reality - Nilam Permatasari Munir; Aswar Anas; Lilis Suryani; Fairus Suryani Munir (Al-Khwarizmi : Jurnal Pendidikan Matematika dan Ilmu Pengetahuan Alam, 2022)
Abstract:Augmented reality geometry applications are developed based on today's learning needs, AR is able to present visualizations of building spaces from the virtual world to the real world through the android camera to the marker. The purpose of this study was to determine the practicality of geometry learning media assisted by the AR android application. This type of research is descriptive quantitative, with a practical questionnaire research instrument. The population of this study were all students of the mathematics study program, 408 students with a simple random sampling technique of 30 students. The technique of analyzing the practicality test data is descriptive statistical analysis. The results show that geometry learning media based on AR android by paying attention to the 6 (six) practical aspects, namely aspects of learning design, media display, software, materials, and benefits are in the very practical category, with a percentage of 94 %. This shows that AR media is very practical for learning.Abstrak:Aplikasi geometri augmented reality dikembangkan berdasarkan kebutuhan pembelajaran dimasa kini. AR mampu menghadirkan visualisasi bangun ruang dari dunia maya ke dunia nyata melalui kamera android ke marker. Penelitian ini bertujuan untuk mengetahui praktikalitas media pembelajaran bangun ruang sisi datar berbantuan aplikasi android AR. Jenis penelitian ini adalah deskriptif kuantitatif, dengan instrumen penelitian angket praktikalitas, populasi dalam penelitian ini adalah seluruh mahasiswa program studi pendidikan matematika sebanyak 408 orang dengan teknik pengambilan sampel simple random sampling sebanyak 30 orang. Teknik analisis data uji praktikalitas yaitu analisis statistic deskriptif. Hasil penelitian ini menunjukkan bahwa media pembelajaran bangun ruang sisi datar  berbantuan aplikasi Android AR dengan memperhatikan ke-6 (enam) aspek praktikalitas yaitu aspek desain pembelajaran, tampilan media, software, materi, dan manfaat, berada pada kategori sangat praktis, dengan persentase sebesar 94%. Hal ini menunjukkan media AR ini sangat praktis digunakan dalam pembelajaran.